2022
DOI: 10.55230/mabjournal.v51i4.06
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic Influences on Tree Species Composition and Community Structure in a Secondary-Lowland Dipterocarp Forest of Kota Damansara Forest Reserve, Selangor

Abstract: This research was conducted to determine tree species composition and its relationship with edaphic factors at Kota Damansara Forest Reserve (KDFR), Selangor. Ten study plots of 25 m × 20 m each were established randomly covering a total area of 0.5 ha. In each plot, all trees with diameters at breast height (DBH) of 5 cm and above were tagged and measured whilst topsoil samples at 10 cm depths were taken for their physical and chemical properties. A total of 205 trees from 46 species and 22 families were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…GIFR recorded the Shannon-Wiener Diversity Index (H') of 2.66 (H'maxa= 2.77) which was lower in comparison to other tropical rainforests (Tablea3). For instance, a study conducted by [21] revealed that Gunung Belumut Recreational Forest has a H' value of 4.82 (H' max = 5.66) whereas Redang Island with H' = 4.05 (H' max = 4.52) [20] and Kota Damansara Forest Reserve at H' = 3.43 (H'max = 4.54) [22]. The low value of the diversity index indicates that GIFR has poor level of species diversity which correlates with the stature of GIFR as a secondary forest.…”
Section: Species Richness Diversity and Evennessmentioning
confidence: 99%
“…GIFR recorded the Shannon-Wiener Diversity Index (H') of 2.66 (H'maxa= 2.77) which was lower in comparison to other tropical rainforests (Tablea3). For instance, a study conducted by [21] revealed that Gunung Belumut Recreational Forest has a H' value of 4.82 (H' max = 5.66) whereas Redang Island with H' = 4.05 (H' max = 4.52) [20] and Kota Damansara Forest Reserve at H' = 3.43 (H'max = 4.54) [22]. The low value of the diversity index indicates that GIFR has poor level of species diversity which correlates with the stature of GIFR as a secondary forest.…”
Section: Species Richness Diversity and Evennessmentioning
confidence: 99%